Inovações em serviços prestados por Instituições de Ensino Superior, frente às condições impostas pelo COVID-19 - Camargo, Joceliane Antunes Araujo (2021)
Innovation is one of the main phenomena in contemporary economies. It is highlighted as a competitive advantage factor and assists to the companies’ survival, featuring as one of the development and growth sources. In view of this context, considering the segmentalist approach to the organizational innovation study, the present study has, as objective, to analyze the perception of the Guarapuava HEIs students about the innovations implemented by them, to confront the conditions imposed by COVID-19. Therefore, it has been identified the innovations implemented by the Higher Educational Institutions during the pandemic period, from the students’ perception. The research methodology is classified as exploratory-descriptive about the objective, with mixed sequenced approach, performed with a case study and survey. The data was collected through semi structured interviews and no-participant observation on the qualitative phase, such as a quiz to the quantitative, thus to its analyzes it has used content analysis and statistical ones. Yet, seeking to understand the searched context, it was interviewed five HEIs workers that have their head office in Guarapuava, and the quiz was answered by a non-probabilistic sample by adhesion composed by 237 students of these institutions. This way, it is concluded that the HEIs have developed several actions, between them the innovations in services and processes, during the COVID-19 pandemic period. Those were observed from the perspective of eight strategy elements of services that have been grouped on three factors, according to the Exploratory Factorial Analysis. In general, the elements services, people, distribution, processes, promotion, show a positive trend from the students’ perspective, but the proposed questions showed moderate agreement. Already referring to the price, productivity/quality and physical evidences, the averages points to the neutrality, because the respondents, being important to highlight that the only question with high agreement concerns the fact that the HEI’s have widely attended the pandemic related demands (distance, use of the alcohol gel and mask, cleaning of collective spaces, etc.). For a more detailed analysis, the average of the factors was separated by institution, this way, it has been identified that the University Centers stand out for better scores, and from the Analysis of Variance it was possible to observe that there are statistically significant differences between some HEIs. Cluster Analysis indicated the existence of two distinct groupings, one with higher averages and the other with lower ones. Thus, the study showed which are the strategic elements that need attention by HEIs, mainly because they influence the customer’s perception of quality.